Answer:
1,3
Step-by-step explanation:
=(x^2-1)(x^2-9)=0
x=1,x=3
3(-13-2)= -45
Step-by-step explanation:
We need to write the equation of:
three times the difference of -13 and 2 amounts to -45 written as an equation
The equation is:
3(-13-2)= -45
Keywords: Convert Sentence into Equations
Learn more about Converting Sentence into Equations:
#learnwithBrainly
Answer:
Step-by-step explanation:
D
Rosetta drove her car 80 miles in one hour. Assuming that you ate talking about miles per hour you decide 160÷2=80 therefore, she drove 80 miles per hour (80/mph)
The answer to this would be C because you can multiply everything by 3 and still have a consistent-dependent system.